Pengaruh Pelapisan Zinc Phosphate pada Baja Karbon ST42 terhadap Laju Korosi dan Ketahanan Aus - Rio Candra Hermawan; Nani Mulyaningsih; M. Fendy Kussuma Hadi Sufyan (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2025)
This study investigates the effect of zinc phosphate coating duration on the corrosion rate and wear resistance of ST42 steel for maritime applications. The experimental method involved immersion at 90°C with time variations ranging from 10 to 30 minutes. Corrosion rate testing utilized the potentiodynamic method (ASTM G102-89) in a 3.5% NaCl solution, while wear resistance was evaluated using the universal wear method (ASTM G99). The results indicate that the lowest corrosion rate occurred at a 30-minute coating duration (0.00678 mmpy), whereas the highest rate was at 10 minutes (0.08600 mmpy). Optimal wear resistance was observed at 20 minutes, yielding a value of 0.000642 mm³/kg·m. In conclusion, zinc phosphate coating effectively enhances the durability of ST42 steel against corrosive environments and mechanical friction. A 30-minute duration is recommended for maximum corrosion protection, providing a viable solution for extending the service life of maritime components such as anchor chains.